Scaffold combination of chitosan and collagen synthesized from chicken feet induces osteoblast and osteoprotegerin expression in bone healing process of mice - Saka Winias; Diah Savitri Ernawati; Maretaningtias Dwi Ariani; Retno Pudji Rahayu (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Over 500.000 of the 2,3 million surgical treatments requiring bone grafting procedures that are performed annually are likely to be necessitated by or will result in bone defects that will not regenerate. Treatment to regenerate new tissues is needed, especially for hard tissue repair, which not only relies on a natural osseointegration process, but also requires a physical support to guide the differentiation and proliferation of cells into the targeted functional tissue. Chitosan and collagen extracted from chicken feet combinations are expected to enhance the bioactive surface and provide mechanical strength as a bone graft scaffold. Purpose: The aim of this study was to investigate the role of chitosan and collagen scaffold synthesized from chicken feet applications to increase the expression of Osteoprotegerin (OPG) and osteoblast cells on the fourteenth day of bone healing. Methods: Eighteen three-month old, adult, male, Rattus novergicu strain rodents with a body weight ranging from 200-350 g were kept under controlled environmental conditions. The mice were randomly divided into three groups consisting of three subjects, each treated with collagen, chitosan, chitosancollagen combination (50:50) scaffolds. On the 14th post-treatment day, three members of each group were sacrificed. Examination of Osteoprotegerin (OPG) expression was conducted by means of immunohistochemistry staining with anti-OPG polyclonal antibodies. Meanwhile, osteoblast cell examination was performed by means of hematoxilin-eosin (HE) staining. Results: The mice treated with collagen and a chitosan-collagen combination scaffold presented an increase in the expression of Osteoprotegerin (OPG) and the number of osteoblast cells respectively. Conclusion: A combination of chitosan-collagen (50:50) scaffold extracted from chicken feet increased the expression of OPG and the number of osteoblasts in the bone healing process. The combination scaffolds demonstrated the highest OPG expression and number of osteoblasts compared to the other groups.